2013
DOI: 10.1145/2543698.2543703
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Vibrotactile Stimulation on the Emotional Response to Horror Films

Abstract: Over the last decade consumers have witnessed a dramatic increase in the use of low fidelity, discrete vibrotactile feedback to enhance or replace audio stimuli in entertainment systems. However, use of highresolution continuous vibrotactile displays remains quite uncommon. The Emoti-Chair is a high-resolution continuous vibrotactile display that may be driven by any type of audio signal, and is purported to convey the emotional properties of sound through organized vibrotactile stimulation. In the current stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…They also observed that not only the intensity of vibration but also the frequency of the vibrotacile stimuli was playing a role in the observed reactions. The present study results are consistent with Branje et al (2013) and further support the hypothesis that both controls and musicians are able to extract meaningful information from the frequency characteristics of a signal presented through vibrations only. Furthermore, for the emotion of peacefulness, results revealed a significant difference between musicians and controls for tactile stimulation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They also observed that not only the intensity of vibration but also the frequency of the vibrotacile stimuli was playing a role in the observed reactions. The present study results are consistent with Branje et al (2013) and further support the hypothesis that both controls and musicians are able to extract meaningful information from the frequency characteristics of a signal presented through vibrations only. Furthermore, for the emotion of peacefulness, results revealed a significant difference between musicians and controls for tactile stimulation.…”
Section: Discussionsupporting
confidence: 90%
“…No study to date has investigated purely tactile identification of emotion in music. The only existing study along these lines was performed by Branje et al (2013) and suggests that multisensory stimulation can increase emotion perception in film. By using the Emoti-Chair, a device that induces vibration in the back of normal-hearing participants, they found increases in skin conductance levels when vibrotactile stimuli were added to audio/visual film content.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the findings suggest that synchronous tactile stimulation can enhance the affective content in music. This interpretation is consistent with findings from Branje et al 12 who found that the addition of tactile stimulation to music induced stronger emotional responses in film music (see also 13 ). Secondly, the tactile stimulation can enhance the music experience by inducing a greater sense of arousal (deeper experience), which was a finding also present in Branje et al 12 Thus, in the liked song with auditory-tactile stimulation, listeners may better experience pleasant emotions associated with their preferred song.…”
Section: Discussionsupporting
confidence: 92%
“… 11 Lastly since listeners can feel the low-frequency vibrations associated with the music’s acoustic energy emitted by speakers (for example) on their skin, tactile stimulation is often used in affective computing to enhance emotions elicited by music. 12 , 13 Here we investigated whether combining auditory and tactile (touch) stimulation by music can enhance pain attenuation.…”
Section: Introductionmentioning
confidence: 99%
“…In music, although there have been numerous studies testing different stimuli and vibrotactile devices, in the world of cinema, this type of research is less abundant. By testing the joint experience of watching horror films and receiving vibrotactile stimulation through a high-resolution continuous vibrotactile display, evidence of emotion augmentation was found [17], although it was based on the subjective emotional response of the participants compiled through a self-reported survey. Moreover, vibrotactile stimulation, generated by a haptic glove prototype, has shown a potential to enhance mood, as different combinations of intensity and frequency seem to elicit different moods [18].…”
Section: Introductionmentioning
confidence: 99%